2023
DOI: 10.1039/d3cc02090h
|View full text |Cite
|
Sign up to set email alerts
|

Solvent–antisolvent interactions in metal halide perovskites

Abstract: This feature article outlines the impact of solvent–antisolvent interactions on the film formation processes of metal halide perovskites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 125 publications
(211 reference statements)
0
4
0
Order By: Relevance
“…The spin-coating of the perovskite precursor solution involves an antisolvent treatment to facilitate the removal of the host solvent(s) molecules and as a consequence initiate the crystallization of the perovskite film. Several studies have reported the optimal conditions for this step, and it has been shown that antisolvent–solvent interactions, such as dipole–dipole interactions, modulate the dynamics of the process . The film morphology is affected by composition-dependent liquid-crystal dynamics and competing crystallization routes that occur during the crucial stages of film formation.…”
Section: Resultsmentioning
confidence: 99%
“…The spin-coating of the perovskite precursor solution involves an antisolvent treatment to facilitate the removal of the host solvent(s) molecules and as a consequence initiate the crystallization of the perovskite film. Several studies have reported the optimal conditions for this step, and it has been shown that antisolvent–solvent interactions, such as dipole–dipole interactions, modulate the dynamics of the process . The film morphology is affected by composition-dependent liquid-crystal dynamics and competing crystallization routes that occur during the crucial stages of film formation.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have reported the optimal conditions for this step, and it has been shown that antisolvent-solvent interactions, such as dipole-dipole interactions, modulate the dynamics of the process. 32 The film morphology is affected by composition-dependent liquidcrystal dynamics and competing crystallization routes that occur during the crucial stages of film formation. To optimize the process, a broad variety of solvents was examined, and it was found that the type of antisolvent used limits the window of operation for morphology and power conversion efficiency (PCE).…”
Section: Resultsmentioning
confidence: 99%
“…The type of antisolvent, the ratio between the precursor solvent and the antisolvent, and the antisolvent dripping time and speed are among key parameters to be considered for enhanced efficiency [37]. Even though the interaction between the solvent and antisolvent or between the precursor and antisolvent is governed by the nature of the antisolvent, an ideal antisolvent is required to be insoluble with both the host solvent and perovskite precursors but also miscible with host solvent [38]. When chlorobenzene was utilized in the fabrication of bismuth-based perovskite films, the result was a decrease in grain size and a modest improvement in surface coverage [39].…”
Section: Introductionmentioning
confidence: 99%